Thermal comfort evaluation inside a car parked under sun and shadow using a thermal manikin. Issue 1 (May 2021) - Danca, P A; Nastase, I.; Croitoru, C.; Bode, F.; Sandu, M.
Abstract: During the summer, vehicle passengers may reach a comfort state, if the sun direct solar radiation do not affect them. Human body parts exposed to the sun, experience a high uncomfortable state which have a direct impact to the global sensation of the all body. The purpose of this study is to deepen the knowledge about the thermal phenomena that occur in cabin and its effects to the thermal state experienced by the driver during a summer sunny. This way we compare temperatures, humidity and Equivalent Temperature (teq ) index acquired with an advanced thermal manikin for 3 scenarios. Results reveals that for a direct solar radiation of 500 Wm −2 temperature inside of the car rise with 10°C. Also, the values of teq for the manikin parts exposed exceed value of 36°C leading to a very hot thermal state for all body.